Penerapan Prenatal Yoga Untuk Mengatasi Nyeri Punggung Akut Pada Ibu Hamil Trimester III - Ridawati, Indah Dewi; Feri, Jhon; Basdafa, Annisa Prayudis Tripanca (JKM : Jurnal Keperawatan Merdeka, 2024)
Background : Back pain is one of the discomforts of pregnant women in the third trimester. If back pain in pregnant women is not treated immediately, it can cause back pain in the long term, increase in back pain after giving birth, and become chronic back pain. Efforts are being made to overcome acute back pain by implementing prenatal yoga. Methods : This research design uses a descriptive research method with a case study approach using 2 people as subjects, namely third trimester pregnant women in the Swasti Saba Community Health Center Work Area in March 2024 for 3 days. The data in this study was taken using interviews and direct observation of pregnant women in the third trimester. Results : The implementation of prenatal yoga carried out on 2 subjects was quite helpful in reducing the back pain scale of pregnant women, for the subject for the first 1 day the back pain scale was 6 (moderate pain) until the last day it dropped to 3 (mild pain) and for the subject for the first 2 days the back pain scale was 5 (moderate pain) until the last day it dropped to 2 (fair pain). Conclusion : The application of prenatal yoga is quite helpful in reducing the level of acute back pain in third trimester pregnant women.